The impact of teaching methods on the performance of geography students in some selected public secondary schools in Zaria local government area, Kaduna State, Nigeria - Abdulkadir Yahaya Muhammed; Abdullahi Lawal Dutsinma; Salamatu Suleiman; Abdulaziz Ahmed (Goodwood Publishing, 2021)
Purpose: This study analyzes the impact of teaching methods on Geography students’ performance in Zaria Local Government Area, Kaduna State, Nigeria. Six senior secondary schools: AlhudaHuda College, Barewa College, Government Secondary School Kofar Kibo, Government Girls Secondary School Kofar Gayan, Government Girls Secondary School Pada and Government Girls Secondary School, Kongo were sampled. Research methodology: 423 questionnaires were administered to respondents. Descriptive statistics and inferential statistics using SPSS version 23 were used to analyze the data. Results: The results revealed that the demonstration method of teaching was the most used by teachers ahead of others (44.6%). The results also revealed that 28.3% of the students who responded say they did not know the teachers’ actual method in teaching them. Limitations: The study used not only Geography teachers as respondents, but also other subjects related to Geography. Additionally, the study covered only Zaria Local Government Secondary Schools. It can be done with only Geography teachers’ respondents in a larger scope like a state or even a country. Contribution: The study will help the Ministry of Education responsible for secondary education and all stakeholders to understand the reality of state of Secondary Education in the study area to address the problems. Additionally, the study can be replicated in other study areas with similar characteristics. Keywords: Impact, Teaching method, Senior secondary schools